Essence of audit and auditing activities (Journal of actual problems of jurisprudence, 2018)
The article dwells on the peculiarities of the auditing activities in the Republic of Kazakhstan and its qualityand characteristics. On the basis of applicable legislation of the Kazakhstan as well as the analysis of theoreticalregulations makes recommendation at improving the audit activities in the Republic of Kazakhstan.Keywords: Audit, auditor activity, audit standards, the Republic Kazakhstan Law «About auditor activity»,essence of audit.